Challenges for implementing water resources planning frameworks based on stochastic modelling assessments: the case for change in England and Wales - Turner, Sean (Cranfield University, 2014)
This research examines the case for change in the regulated water resources planning process in England and Wales. The primary contribution to knowledge is delivered through the identification of practical, conceptual and institutional challenges associated with emerging planning methods based on stochastic modelling assessments. Four alternative modelling trials are executed and then compared to existing practice using real-world water resources systems. In-depth, structured interviews capture the views of a range of practitioners closely involved in the planning process. The study finds that the trialled approaches are technically feasible and can be executed using existing models and freely-available data. This finding counters the widespread view—exposed during interviews—that water companies are ill-equipped to conduct stochastic modelling assessments. However, some of the purported benefits of these frameworks failed to materialise in the case analyses. The study identifies arbitrary assumptions that threaten the transparency and rigour of the emerging methods. The practitioner interviews highlight widespread scepticism and perceived business risks associated with a shift away from deterministic planning. The thesis also delivers a number of methodological developments and is structured using a simple, novel matrix that characterises water availability assessment methods according to the way performance is measured and the way hydrological uncertainty is treated.
Appendices available on CD from Kings Norton Library